The Effect Of Capital Stucture, Liquidity And Company Size On Profitability In Islamic Commercial Banks In Indonesia - dara, Risma; Busra; Yulianisah (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2024)
Profitability is the company's ability to generate profits. Many phenomena that occur in this study are that there are still differences in research results between researchers, although the research is still within the scope of 1 sector with the same variables but obtains different results. The purpose of this study is to test the effect of capital structure, liquidity and company size on profitability in Islamic commercial banks in Indonesia for the period 2018-2022. The sample was selected using a purposive sampling technique, so that 45 were collected. This study uses a panel data regression analysis method. The selected model is the common effect model. The results of the study partially show that capital structure has a negative effect on profitability, liquidity has a negative effect on profitability and company size has a significant positive effect on profitability. Simultaneously shows that capital structure, liquidity and company size on profitability in Islamic commercial banks in Indonesia. that the size of a large company can be seen from its total assets. the larger the company's assets, the easier or freer the company's management will be in managing and using these assets in carrying out the company's operational activities. the flexibility and ease of management in controlling assets will be able to increase Profitability Keywords : capital structure, liquidity and profitability company size